Synthesis, characterization, and antibacterial activity of Ni(II) complex bearing salen ligand - Mohammed A. Al-Wahish (Pharmacia)
A new nickel(II) complex, (Ni(L)), based on the Schiff base ligand cis-N,N-bis-(2’,4’-dihydroxybenzylidene)-1,2-diaminocyclohexane (H₂Salen), was synthesized and characterized using FT-IR, ¹H and ¹³C NMR, and elemental analysis. The ligand also formed Co(II) and Cu(II) complexes with distinct geometries: distorted octahedral for Ni(II) and Co(II) and distorted square planar for Cu(II). This study aimed to evaluate the antimicrobial activity of the ligand and its complexes against Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative). Using CLSI protocols, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined. All metal–salen complexes exhibited bacteriostatic activity, with Ni(II) being the most effective. Chelation increased lipophilicity and acidity–enhancing bacterial inhibition by disrupting cellular processes. Differences in activity between strains were attributed to variations in cell wall composition. The findings demonstrate that metal complexation significantly improves antimicrobial potency compared to the free ligand and support further investigation of these compounds for pharmaceutical and industrial antimicrobial applications.